7x-3(-x-6)=-32

Simple and best practice solution for 7x-3(-x-6)=-32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3(-x-6)=-32 equation:


Simplifying
7x + -3(-1x + -6) = -32

Reorder the terms:
7x + -3(-6 + -1x) = -32
7x + (-6 * -3 + -1x * -3) = -32
7x + (18 + 3x) = -32

Reorder the terms:
18 + 7x + 3x = -32

Combine like terms: 7x + 3x = 10x
18 + 10x = -32

Solving
18 + 10x = -32

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 10x = -32 + -18

Combine like terms: 18 + -18 = 0
0 + 10x = -32 + -18
10x = -32 + -18

Combine like terms: -32 + -18 = -50
10x = -50

Divide each side by '10'.
x = -5

Simplifying
x = -5

See similar equations:

| 7(4+3x)=-238 | | 8x-2x-10=2x-2 | | 7x-3(2x-7)=-25 | | 8x+32=65+5x | | P7/10=392 | | -2-5(2x-7)=-25 | | 6/21= | | 2y^2+9wy+7w^2=0 | | 3x-2x=4x-3/2 | | -4x+2(6x+7)=-74 | | -7x+5(-4x-9)=90 | | -7x-6(-x-4)=13 | | 1/3-2/6 | | 5/18×6/35 | | (2/3)x-2=(7/9)x | | 22+0.35=c | | 3x+7(-x+3)=-7 | | x+.04x=20 | | 3x+12+2x=5+4x | | x-.2x=240000 | | p=-q^2+8q+10 | | 2x+3(5x+8)= | | 2(x+3)-4=16 | | (-5+5w+2v)(-6)= | | 15x^5+6x^3=-20x^4-8x^2 | | 8x-(6x-2)=2 | | 18v-(8v-7)=67 | | 3/5w-7/3=-5/2 | | -2y+24=6 | | -4(n+2)=(n-4) | | 1/2×12 | | 10m^2-21m-6=0 |

Equations solver categories